Is high‐frequency ultrasound a useful process to add value to out of specification strawberries, raspberries and blackberries industrially?. (19th August 2022) - Hooper, Matthew; McNeilly, Alison D.; Schaschke, Carl; Wilkin, Jonathan D.
Summary: Bioactive ingredients can be extracted from surplus soft fruits to add value to them as a fortification ingredient in many new products. Ultrasound‐assisted extraction and spray drying have been heavily studied in the past, with evidence to suggest the positive uptake of these by the food industry. In this paper, strawberries, raspberries and blackberries were examined using a distilled water 'green' extraction method with assisted high‐frequency ultrasound and concentration through spray drying. The results showed that crop year and variety had more impact on bioactive concentration than extraction through high‐frequency ultrasound. Two different machines were examined for differences between a cold extraction of water, and a 700 and 2000 Hz industrially relevant probes. Typically, total phenolic content (TPC) was lower in strawberries and blackberries than the control for both methods, however raspberries had a higher GAE mg ml−1 for the 2000 Hz ultrasound than the control. For Radical scavenging (RS) percentage using DPPH Blackberries had higher RS % than the control, whereas strawberries and raspberries had less than the control. These results suggest that ultrasound as a singular method for extracting valuable bioactive ingredients is not suitable with water as the solvent. Abstract : Yield % of extracted bioactive fruit from crop year, variety of fruit (strawberry, blackberry and raspberry) and treatment with or without ultrasound.